Numerical solution of Volterra‐Fredholm integral equation via hyperbolic basis functions. (11th November 2020) - Esmaeili, Hamid; Rostami, Majid; Hooshyarbakhsh, Vahideh
Abstract: In this paper, a new method using hyperbolic basis functions is presented to solve second kind linear Volterra‐Fredholm integral equation. In other words, our method approximates the solution of a Volterra‐Fredholm integral equation by the hyperbolic basis functions, which produce block‐pulse functions. Hence, the new method reduces the linear Volterra‐Fredholm integral equation to a system of algebraic equations. Some numerical examples are provided to illustrate the computational efficiency and accuracy of the new method.